2011
DOI: 10.1007/bf03395749
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Reliability of Delay Discounting of Ten Commodities Using the Fill-in-the-Blank Method

Abstract: Key words: delay discounting, reliability, fill-in-the-blank method, different commodities, college students Delay discounting refers to the finding that when an outcome is delayed, its value is decreased. For instance, most individuals would accept $95 today rather than waiting 1 year for $100, indicating that the delay of 1 year has decreased the value of the larger amount by at least $5. The study of delay discounting has been widespread (e.g., Takahashi, Masataka, Malaivijitnond, & Wongsiri, 2008;Whelan & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…This is consistent with previous research results (10, 11, 13). It suggests that delay discounting, apart from risk discounting, might be more of a personality trait.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with previous research results (10, 11, 13). It suggests that delay discounting, apart from risk discounting, might be more of a personality trait.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with this thought, only a few studies that used test-retest designs indicated that delay discounting was stable over time in healthy volunteers [e.g., (1012)]. Studies in addicted patients were even fewer and less conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Participants answered this question by typing in the amount of money they would accept today rather than waiting, a procedure called the fill-in-the-blank method (Chapman, 1996). This particular method of measuring delay discounting has been shown to be reliable (Weatherly, Derenne, & Terrell, 2011), as well as to be sensitive to differences in discounting across outcomes (e.g., Chapman, 1996;. Participants answered this question five times, with the questions differing in the amount of time before the $1,000 became available.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Since it requires individuals to make a large number of choices, it is time-consuming and usually requires computer access. Some have argued that its ecological validity could be improved, since individuals typically focus on only one choice of interest and not an extensive series (Weatherly et al (2011)). …”
Section: Developing Laboratory Tasks For Adolescentsmentioning
confidence: 99%